Functional Plasticity of Gamma Delta T Cells and Breast Tumor Targets in Hypoxia - Siegers, Gabrielle M.; Dutta, Indrani; Lai, Raymond; Postovit, Lynne-Marie (Frontiers in Immunology, 2018)
Interactions between immune and tumour cells in the tumour microenvironment (TME) often impact patient outcome, yet remain poorly understood. In addition, the effects of biophysical features such as hypoxia [low oxygen (O2)] on cells within the TME may lead to tumour evasion. Gamma delta T cells (γδTc) naturally kill transformed cells and are therefore under development as immunotherapy for various cancers. Clinical trials have proven the safety of γδTc immunotherapy and increased circulating γδTc levels correlate with improved patient outcome. Yet, the function of γδTc tumor infiltrating lymphocytes (TIL) in human breast cancer remains controversial. Breast tumours can be highly hypoxic, thus therapy must be effective under low O2 conditions. We have found increased infiltration of γδTc in areas of hypoxia in a small cohort of breast tumours; considering their inherent plasticity, it is important to understand how hypoxia influences γδTc function. In vitro, the cell density of expanded primary healthy-donor blood-derived human γδTc decreased in response to hypoxia (2% O2) compared to normoxia (20% O2). However, the secretion of MIP1α/MIP1β, RANTES and CD40L by γδTc were increased after 40 hours in hypoxia compared to normoxia concomitant with the stabilization of Hypoxia Inducible Factor 1-alpha (HIF1α) protein. Mechanistically, we determined that NKG2D on γδTc and the NKG2D ligand MICA/B on MCF-7 and T47D breast cancer cell lines are important for γδTc cytotoxicity, but that MIP1α, RANTES and CD40L do not play a direct role in cytotoxicity. Hypoxia appeared to enhance the cytotoxicity of γδTc such that exposure for 48 hours increased cytotoxicity of γδTc against breast cancer cells that were maintained in normoxia; conversely, breast cancer lines incubated in hypoxia for 48 hours prior to the assay were largely resistant to γδTc cytotoxicity. MICA/B surface expression on both MCF-7 and T47D remained unchanged upon exposure to hypoxia; however, ELISAs revealed increased MICA shedding by MCF-7 under hypoxia, potentially explaining resistance to γδTc cytotoxicity. Despite enhanced γδTc cytotoxicity upon pre-incubation in hypoxia, these cells were unable to overcome hypoxia-induced resistance of MCF-7. Thus, such resistance mechanisms employed by breast cancer targets must be overcome to develop more effective γδTc immunotherapies.